Ham-let : a Shakespearean mash-up - Burnstein, Jim; Schiff, Garrett K. (Dark Horse Books, 2022)
In this twist on Shakepeare's Hamlet, the eponymous Pig Prince himself returns home from college to find that his uncle Claude betrayed and murdered his father to seize the throne.